2016
DOI: 10.1038/leu.2016.260
|View full text |Cite
|
Sign up to set email alerts
|

BET protein bromodomain inhibitor-based combinations are highly active against post-myeloproliferative neoplasm secondary AML cells

Abstract: Myeloproliferative Neoplasms with myelofibrosis (MPN-MF) demonstrate constitutive activation of JAK-STAT signaling, which responds to treatment with the JAK1 & 2 kinase inhibitor (JAKi) ruxolitinib. However, MPN-MF often progresses (~20%) to secondary AML (sAML), where standard induction chemotherapy or ruxolitinib is relatively ineffective, necessitating the development of novel therapeutic approaches. In the present studies, we demonstrate that treatment with BET (bromodomain and extra terminal) protein inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 53 publications
(104 reference statements)
5
55
0
Order By: Relevance
“…In plasmacytomas arising from Gp130 activation alone, activating genetic alterations in the c-MYC locus were recovered in three of ten independently arising tumors (33). Combining JAK and BET inhibitors is a potentially promising strategy for other hematologic malignancies, including JAK2V617-dependent myeloproliferative neoplasms and acute lymphocytic leukemia (ALL) characterized by IL7R activation (35)(36)(37)(38). In the ALL models, JQ-1 suppressed STAT5dependent signaling and improved survival; significantly at relapse, these tumors showed reactivation of STAT5 signaling indicating a feedback upregulation of JAK-STAT signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In plasmacytomas arising from Gp130 activation alone, activating genetic alterations in the c-MYC locus were recovered in three of ten independently arising tumors (33). Combining JAK and BET inhibitors is a potentially promising strategy for other hematologic malignancies, including JAK2V617-dependent myeloproliferative neoplasms and acute lymphocytic leukemia (ALL) characterized by IL7R activation (35)(36)(37)(38). In the ALL models, JQ-1 suppressed STAT5dependent signaling and improved survival; significantly at relapse, these tumors showed reactivation of STAT5 signaling indicating a feedback upregulation of JAK-STAT signaling.…”
Section: Discussionmentioning
confidence: 99%
“…They are the only domains, which bind specifically to histone acetylation marks (Jain & Barton, 2017). Recently, the anti-cancer efficacy of inhibitors against the bromodomain and extra-terminal domain-containing (BET) protein family have been evaluated in several cancers, such as prostate, breast, colon, intestine, pancreas, liver, lung, brain, oral squamous cell carcinoma, and leukemias (Sahai et al, 2016;Saenz et al, 2017;Xu & Vakoc, 2017;Sahni & Keri, 2018;Zhang et al, 2018;Baldan et al, 2019). Even though combined treatment with HDAC and BET inhibitors (BETi) revealed additive or synergistic effects in several cancer entities, such as cutaneous T-cell lymphoma, neuroblastoma, glioblastoma, non-small cell lung cancer, adenocarcinoma, and colon cancer (Mazur et al, 2015;Shahbazi et al, 2016;Adeegbe et al, 2017;Meng et al, 2018;Rajendran et al, 2019;Zhao et al, 2019), so far only few studies described the mono-and combined treatment options with BETis in GCTs.…”
Section: Hdac Inhibitors Plus Bromodomain Protein Inhibitorsmentioning
confidence: 99%
“…S5A and S5B). Mice bearing xenograft tumors were then treated daily (including a 1-to 2-day drug holiday per mouse) with subcutaneous administration of vehicle or 30 mg/kg ARV771, a BET PROTAC with confirmed in vivo efficacy (56)(57)(58). We observed that this treatment regimen was well-tolerated in both cohorts ( Supplementary Fig.…”
Section: Genetic Inhibition Of Brd4 Improves Bet Inhibitor Therapeutimentioning
confidence: 86%